Emotional priming depends on the degree of conscious experience. (May 2019) - Lohse, Michael; Overgaard, Morten
Abstract: Most experiments in consciousness research assume that awareness is a dichotomous 'either/or' phenomenon. However, participants can distinguish multiple levels of subjective experience of simple features (colour, shape etc.), which correlate with their performance in different tasks. As experiments showing multiple levels of perceptual awareness question the widespread idea that many forms of perception can occur unconsciously, we investigated emotional priming combined with methods able to measure small variations in subjective experience. We show awareness of emotional faces is gradual rather than dichotomous, and that the effects of emotional priming are predicted by the level of perceptual awareness of emotional faces, with no effects when reported unseen. The results question how much unconscious perceptions can influence behaviour. As priming is one of the most well-established phenomena believed to occur unconsciously, the results expand the growing body of evidence that questions the contributions of unconscious processing on behaviour. Highlights: Emotional priming is considered fundamental evidence for unconscious perception. Emotional priming strength is predicted by graded perceptual awareness levels. Emotional priming with faces is not effective when faces are reported as unseen. Facial expression recognition increases gradually with perceptual awareness levels. Perceptual awareness of faces increases gradually with duration of face stimuli.